Analysis of Ran/TC4 function in nuclear protein import - Melchior, Frauke; Sweet, Deborah J.; Gerace, Larry (Small GTPases and their regulators ; Pt. C: Proteins involved in transport, 1995)
This chapter describes an alternative enzyme-linked immunosorbent assay (ELISA) based quantitative assay for nuclear import and its use for studying the role of Ran/TC4 in the import process. This assay measures the protein transported in 105-106 cells per sample by a colorimetric method that allows straightforward calculation of the number of molecules transported per cell. It also has the advantage of not requiring any specialized or expensive equipment other than an ELISA plate reader. Ran/TC4 defines an evolutionarily well-conserved branch of the Ras superfamily whose exact function(s) remains unclear. It is found in both the nucleus and cytoplasm, and, in contrast to other GTPases of the Ras superfamily, is not posttranslationally modified. Several interacting proteins have been molecularly cloned.
Online veröffentlicht: 7. Januar 2004
Gesehen am 07.09.2023